The Effect of Service on Customer Satisfaction at PT Pandu Siwi Sentosa - M. Edwin Tri Oktareza; Hamid Halin; Susi Handayani (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
This study aims to measure the effect of service on customer satisfaction at PT Pandu Siwi Sentosa. Data were collected through questionnaires on 50 PT Pandu Siwi Sentosa consumers and analysed using simple linear regression. The results of the investigation prove that service has a positive and significant effect on customer satisfaction. The coefficient of determination of 0.577 indicates that service contributes 57% to customer satisfaction, while the remaining of 43% is explained by other variables not included in this study. Based on the results, the decision holders at PT Pandu Siwi Sentosa should improve the quality of service to increase the level of customer satisfaction.